Match internal load in wheelchair basketball games - an exploratory study - Seron, B. B.; de Carvalho, E. M. O.; Souto, E. C.; Figueiredo, D. H.; Figueiredo, D. H.; Greguol, M. (International Journal of Performance Analysis in Sport, 2025)
This study aimed to compare the match internal load according to the type of disability at different moments in the wheelchair basketball game and the effect of playing the last 5 min of the half on Lactate (LA+) concentrations. Thirty athletes (34.4 ± 6.8 years) from 5 wheelchair basketball Brazilian teams were analysed during five official games. For the analyses, athletes were separated by disability [spinal cord injury, polio sequels and lower limb amputation]. A generalised estimating equation analysis was performed to verify the effects of moment, disability and playing the last 5 min of each period on the La+ concentrations. No significant differences were found between disability groups for the TRIMP and the La+ concentrations at different moments in the game. The results pointed out that unbalanced games seem to cause higher lactate concentrations in the first period of the game, especially in players who end up playing in the second quarter. Finally, unbalanced games, whether the player finishes playing the game, seems not to influence the final lactate concentrations. The internal load of the WB game does not differ in the different disabilities, and, in unbalanced games, the players finish the game with low concentrations of lactate.